Mapping of Global Research on Climate Change and the Agricultural Sector: A Bibliometric Analysis 2000-2025 - Judijanto, Loso (West Science Agro, 2025)
This study presents a comprehensive bibliometric analysis of global research on climate change and the agricultural sector published between 2000 and 2025, using the Scopus database as the primary data source. A total of publications retrieved through a targeted keyword search were analyzed using VOSviewer to map co-authorship networks, keyword co-occurrence, citation patterns, and thematic clusters. The results reveal agriculture as the central conceptual hub, linking critical themes such as food security, agricultural productivity, climate change adaptation, biosafety, public policy, and gender empowerment. Thematic evolution indicates a shift from early biophysical impact assessments toward more integrated approaches that combine technological innovation, governance frameworks, and socio-economic equity considerations. Collaboration network analysis highlights France as a key bridging country connecting European, African, and Latin American research communities. Practical implications include the need to strengthen interdisciplinary integration, foster cross-regional partnerships, and address thematic gaps—particularly in linking social equity with climate adaptation strategies. This study contributes theoretically by clarifying the intellectual structure and research trends of the field, while its methodological approach offers a replicable framework for bibliometric mapping in sustainability-related domains. Limitations include database coverage, keyword constraints, and the inability to assess the qualitative rigor of individual studies. The findings provide an evidence base to inform policy priorities, funding allocation, and future research agendas in building climate-resilient and low-emission agrifood systems.